Integrating microwave heating pre-treatment to improve torrefaction of food waste - Mazni, Ismail; Ruwaida, Abdul Rasid; R. N. U., Abdul Rahman; N. S., Ahmad; M. A. W., Mohd Radzuan (Universiti Malaysia Pahang, 2019)
The municipal solid waste (MSW) disposal is one of the main issues of concern, as it affects environmental and sustainable development in Malaysia. Food waste (FW) is the highest constituent in the MSW and should be utilized to produce more valuable products such as energy. However, FW is characterized by its high moisture content and low high heating value (HHV) which lower the energy efficiency during energy production process. In order to overcome this problem, torrefaction assisted by microwave heating pre-treatment is used to upgrade FW properties to produce solid biofuel which is called as biochar. The objective of this study is to investigate the feasibility of microwave (MW) heating power at 240 W for 5 min to enhance the quality of torrefied FW. The torrefied FW was then characterized in terms of ultimate and proximate analysis, HHV, mass and energy yield as well as its functional groups. The highest HHV achieved was 24.21 MJ/kg when torrefied at 320 °C for 45 min. This suggests that torrefied FW with MW heating pre-treatment has the potential to be used as an energy source.